ANALYSIS OF THE INFLUENCE OF PROFIT PERSISTENCE AND GOOD CORPORATE GOVERNANCE ON PROFIT QUALITY IN COMPANIES IN THE BASIC AND CHEMICAL INDUSTRIES SUB-SECTORS TERDAFTARDI ON PERIOD 2019 – 2023 - Br Ginting, Wulan Febriyanti; Simanjuntak , Arthur; Simanjuntak, Gracesiela Yosephine; Sagala, Lamria; Silitonga, Ivo Maelina (Jurnal Ilmiah Accusi, 2025)
This study was conducted to test and analyze the influence of profit persistence, independent commissioners, managerial ownership, and institutional ownership on the quality of corporate profits in the basic and chemical industry subsectors listed on the Indonesia Stock Exchange. This study applies secondary data obtained from financial documents and the company's annual report. The data analysis method applied was multiple linear regression with a sample of 29 companies out of a total of 75 companies that met the research criteria. The analysis was carried out using SPSS version 26. The results of the study showed that profit persistence had a negative and significant impact on the quality of profit, while independent commissioners, managerial ownership, and institutional ownership had a positive and significant impact. The F test shows that all of these variables together affect the quality of profits. However, independent variables only explain 10.2% of profit quality, while the remaining 89.8% are explained by factors outside of this study model. These findings provide a new perspective on how corporate governance and profit persistence affect profit quality, especially in the context of companies in the basic and chemical industries sub-sectors in Indonesia